1997
DOI: 10.21273/hortsci.32.3.487d
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Biofertilizers for `Red Roomy' Grapevines (Vitis vinifera L.): 2. The Effect of Berry Set, Yield, and Quality of Berries

Abstract: The positive influence of fertilizing `Red Roomy' grapevines with four biofertilizers (active dry yeast, phosphorene, rhizobacterium, and nitrobein) on berry set and productivity was investigated during 1995 and 1996. The improvement occurred in berry set and yield, as well as physical and chemical properties in vines treated with the four biofertilizers in the following ascending order: active dry yeast, nitrobein, rhizobacterium, and phosphorene. Highly significant differences in characters were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…Warring and Philips (1973) stated that bread yeast is rich in tryptophan which consider precursor of IAA which stimulate cell division and elongation. Similar results to the present study was found by Mahmoud (1996) on Roomy Red Grapevines and by Akl et al, (1997) al., (2000a) on King Ruby and Gaser et al, (2006) on Flame seedless who found that bread yeast applications significantly increased the yield/vine.…”
Section: Yield and Physical Characteristics Of Clusterssupporting
confidence: 94%
“…Warring and Philips (1973) stated that bread yeast is rich in tryptophan which consider precursor of IAA which stimulate cell division and elongation. Similar results to the present study was found by Mahmoud (1996) on Roomy Red Grapevines and by Akl et al, (1997) al., (2000a) on King Ruby and Gaser et al, (2006) on Flame seedless who found that bread yeast applications significantly increased the yield/vine.…”
Section: Yield and Physical Characteristics Of Clusterssupporting
confidence: 94%
“…The present results are in harmony with those obtained by Akl et al (1997) who found an improvement occurred in berry set of Red Roomy grapevines treated with active dry yeast. Similar results mentioned by Ismaeil et al (2003) who found that spraying yeast extract significantly increased number of berries/cluster on the tested Red Roomy grapevines.…”
Section: Iv-number Of Berries Per Clustersupporting
confidence: 93%
“…Likewise, Omran et al (2005) with Thompson seedless grapevines found that yeast application increased TSS/acid ratio and decreased total acidity. Moreover, Akl et al (1997) with Red Roomy grapevines found an improvement of total soluble solids and total acidity in juice by active dry yeast treatment.…”
Section: I-soluble Solids Content Percentage (Ssc%) Total Acidity Content (%) and Soluble Solids Content / Acid Ratio In Berry Juicementioning
confidence: 92%
“…The concerned results were supported by findings of several researchers Akl et al (1997) on grapevine, Kabeel et al (2008) on pear, El-Naggar (2009) on apricot trees; Abou-Grah-Fatma (2004) and Sharaf et al (2012) on persimmon trees. Table (3): Fruit weight, fruit volume and fruit firmness of "Anna" apple trees in response to organic and bio-fertilizers during both 2013 and 2014 seasons.…”
Section: Treatmentssupporting
confidence: 79%